Development of Moodle-Based E-Learning Media on the Topics of Atomic Structure - Amalia, Irma; Sari, Ratih Permana; Hasibuan, Molani Paulina; Nazar, Muhammad (Jurnal Pendidikan MIPA, 2022)
The goal of this study is to develop e-learning media based on Moodle for atomic structure material, as well as to determine the feasibility of the media and the teacher's response to it. With the ADDIE method derived from Dick and Carrey, this study is included in Research and Development (R&D). Media experts, materials experts, and chemistry teachers are among the study's subjects. Expert validation questionnaires and teacher response questionnaires. The study's findings were that e-learning media based on moodle on atomic structure material had a media feasibility score of 92.8 percent with very feasible criteria and a material feasibility score of 91.7 percent with very feasible criteria. The responses chemistry teachers from Langsa Senior High School yielded an average of 87 percent with very interesting criteria. On the basis of these findings, it can be stated that the Moodle-based e-learning media designed for the atomic structure material is suitable for use in the learning process.Keywords: e-learning, learning media, moodle, development, atomic structure DOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp25-33